PENGARUH CYBERBULLYING TERHADAP TINGKAT KECEMASAN DAN DEPRESI REMAJA DI SEKOLAH MENENGAH - Fitriani, Nurul; Jamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the profound impact of cyberbullying on the mental health, specifically anxiety and depression levels, and academic performance of adolescents in Indonesian secondary schools. The rapid adoption of digital platforms has unfortunately turned cyberspace into a new arena for aggressive behavior, where the unique characteristics of anonymity, permanence, and broad reach intensify the psychological distress experienced by victims. Findings consistently reveal a significant correlation: victims of cyberbullying report substantially higher levels of anxiety and depression compared to their non-victimized peers. This emotional toll is mediated by factors such as chronic stress, fear of public humiliation, and feelings of helplessness, directly eroding self-esteem and overall psychological well-being. Furthermore, the internalizing disorders resulting from cyberbullying—anxiety and depression—act as crucial mediators, subsequently leading to a decline in academic outcomes, including reduced motivation, impaired concentration, and increased school absenteeism. The study underscores the urgency for holistic and integrated interventions that combine robust digital literacy programs, accessible mental health support within schools, and strengthened parental involvement to effectively mitigate the damaging effects of cyberbullying and safeguard the comprehensive well-being of adolescents.